2020
DOI: 10.1242/bio.048173
|View full text |Cite
|
Sign up to set email alerts
|

MACF1 promotes preosteoblast migration by mediating focal adhesion turnover through EB1

Abstract: Microtubule actin crosslinking factor 1 (MACF1) is a widely expressed cytoskeletal linker and plays an essential role in various cells' functions by mediating cytoskeleton organization and dynamics. However, the role of MACF1 on preosteoblast migration is not clear. Here, by using MACF1 knockdown and overexpressed MC3T3-E1 cells, we found MACF1 positively regulated preosteoblast migration induced by cell polarization. Furthermore, immunofluorescent staining showed that MACF1 increased end-binding protein (EB1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…FAK/Src-dependent phosphorylation of MACF1 is required for its binding to F-actin, its coordination of actin dynamics at focal adhesions and its pro-migratory role in skin epidermis ( Yue et al, 2016 ). MACF1 is also robustly expressed in osteoblasts and can regulate preosteoblast migration by mediating FA turnover through the + TIPs EB1 ( Su et al, 2020 ). MACF1 enhances preosteoblast polarization and migration by increasing MT stabilization at FAs.…”
Section: Signaling By Macf1 In Physiological Conditionsmentioning
confidence: 99%
“…FAK/Src-dependent phosphorylation of MACF1 is required for its binding to F-actin, its coordination of actin dynamics at focal adhesions and its pro-migratory role in skin epidermis ( Yue et al, 2016 ). MACF1 is also robustly expressed in osteoblasts and can regulate preosteoblast migration by mediating FA turnover through the + TIPs EB1 ( Su et al, 2020 ). MACF1 enhances preosteoblast polarization and migration by increasing MT stabilization at FAs.…”
Section: Signaling By Macf1 In Physiological Conditionsmentioning
confidence: 99%
“…In accordance with the elevated microtubule dynamics, de-tyrosinated tubulin staining around myonuclei is lost in Macf1 KO muscles ( Figure 3 ), supporting a link between microtubule dynamics and myonuclei motion. No direct interplay between MACF1 and tubulin post translational modification (PTMs) has been so far documented, but one can hypothesize that regarding already described MACF1 localization, at the Minus-End of microtubules throught CAMSAP/patronin or at the Plus-End of microtubules throught EB1, MACF1 can influence localization of enzymes controlling tubulin PTMs such as TTL or SVBP ( Aillaud et al, 2017 ; Noordstra et al, 2016 ; Peris et al, 2006 ; Su et al, 2020 ). Thus, it is tempting to postulate that in MACF1-depleted myofibers from old mice, this elevated microtubule dynamic is constantly challenging the cohesion between myofibrils through Desmin reorganization, hence contributing to the myonuclei internalization process ( Heffler et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that MACF1 is a critical factor in modulating actin and microtubule cytoskeletal networks and regulating cytoskeletal distribution, cell migration, cell survival and cell differentiation [40]. It was reported that MACF1 correlates with various physiological and pathological processes [41]. MACF1 has a signi cant effect on osteogenesis the differentiation of primary osteoblasts [42].…”
Section: Discussionmentioning
confidence: 99%